1991
DOI: 10.2527/1991.691230x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of energy source fed to sows during late gestation on neonatal blood metabolite homeostasis, energy stores and composition.

Abstract: Four experiments utilizing 49 primiparous and 34 multiparous sows were conducted to evaluate the effect of feeding either starch, soybean oil or medium-chain triglyceride (MCT) during late gestation (d 100 to parturition) on neonatal fasting blood glucose homeostasis (Exp. 1 and 2), d-100 maternal circulating insulin, glucagon and glucose concentrations (Exp. 3 and 4), neonatal energy stores (Exp. 3 and 4) and colostrum composition (Exp. 1, 2, 3 and 4). In all cases, sows were fed 7.2 Mcal/d of a diet that sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
17
3

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 0 publications
7
17
3
Order By: Relevance
“…The increased fat content was also reflected in the increased DM content at 24 and 36 h in SOYO-fed sows. This is in line with previous studies, where colostrum and/or milk fat content of sows fed SOYO was greater than for sows fed iso-energetic amounts of medium-chain triglycerides (Newcomb et al 1991;Azain 1993;Jean and Chiang 1999). A lower digestibility of Low fiber content (CON), sugar beet pulp (SBP) and alfalfa meal (ALF).…”
Section: Effect Of Fatsupporting
confidence: 78%
See 1 more Smart Citation
“…The increased fat content was also reflected in the increased DM content at 24 and 36 h in SOYO-fed sows. This is in line with previous studies, where colostrum and/or milk fat content of sows fed SOYO was greater than for sows fed iso-energetic amounts of medium-chain triglycerides (Newcomb et al 1991;Azain 1993;Jean and Chiang 1999). A lower digestibility of Low fiber content (CON), sugar beet pulp (SBP) and alfalfa meal (ALF).…”
Section: Effect Of Fatsupporting
confidence: 78%
“…Jean and Chiang (1999) and Azain (1993) found increased survival, especially of small piglets, from sows fed MCFA compared with SOYO diets. The underlying mechanism for this beneficial effect of dietary fat source on pig survival is not known but may involve piglet blood metabolite homeostasis and/or energy stores at birth (Newcomb et al 1991). Results from the current study do not suggest that the potential effect of MCFA on piglet survival reported by others is mediated directly by increased colostrum intake of piglets.…”
Section: Piglet Survivalcontrasting
confidence: 36%
“…Boyd et al (1978) fed gilts and older sows with a conventional diet until day 99 of gestation and then, from day 100 one of two isoenergetic diets containing either 20% tallow or 32% corn starch were fed until parturition without affecting glycogen deposition or piglet survival. Newcomb et al (1991) studied glycogen deposition in newborn piglets from sows fed one of three different diets from day 100 of gestation until parturition. The diets supplied equal amounts of energy and protein but differed in energy source (274 g wheat starch, 157 g soybean oil or 157 g medium-chain triglyceride/kg of diet).…”
Section: Attempts To Increase Glycogen Depots By Sow Nutritionmentioning
confidence: 99%
“…Oils in sow diets during early-to-mid gestation established; bearing in mind that supplementation was given during the first 60 days of gestation only, there are a number of ways in which the increased litter size may be explained: (i) the fatty acid profile of the diet may alter maternal endocrine status (Hornstra and Stegan, 1989), which in turn may affect embryonic survival and the efficiency of placental development; (ii) palm oil is a rich source of the anti-oxidants b-carotene and vitamin E (Duran, 2002;Edem, 2002) and increased intake of vitamin E has previously been linked to increased litter size in pigs (Mahan, 1991;Pinelli-Saavedra, 2003); (iii) palm oil supplementation may result in glucose sparing in the mother, allowing greater glucose availability for the placenta/foetuses as seen in humans and rats (Kim et al, 1995;Jaquier, 1998;Melanson et al, 1999); (iv) palmitic acid (16:0), primarily from the diet during the first half of gestation, but also from lipolysis of maternal adipose tissue during late pregnancy, may be converted into ketones and improve energy availability to the developing placenta/foetuses (Secombe et al, 1977;Shambaugh, 1985) resulting in better piglet metabolic status at birth (Newcomb et al, 1991;Azain, 1993); and (v) the fatty acids present in palm oil may be …”
Section: --mentioning
confidence: 99%